A Hero in the Friendly Arctic: Deconstructing Vilhjalmur Stefansson’s Rhetorical Maneuver - Gaupseth, Silje (Nordlit, 2012)
The article deals with Arctic explorer and anthropologist Vilhjalmur Stefansson's self-presentation in the expedition account The Friendly Arctic: The Story of Five Years in Polar Regions (1921), which tells the story of his travels and trials in the Canadian High Arctic in the years between 1913-1918. The account has been considered a key text to Stefansson's Arctic career, and provides a textbook example of his characteristic theory of living off the country in the so-called Eskimo way. Against the background of Stefansson's debated position as Arctic expert and visionary, I ask if it is possible to read the kind of criticism with which Stefansson frequently was met as rooted in some of the narrative aspects of his account. The narrative persona or implied author is a central element in the literature of exploration, as several literary scholars have pointed out. My reading is centred around the implied author of The Friendly Arctic, which I argue must be read in light of the sometimes conflicting roles given to Stefansson as protagonist and narrator in his own story. Close-readings of passages from the account raise the dilemma of how it is possible to present oneself as a hero in an essentially friendly Arctic.